Effects of Anthropogenic Loads on Vegetation Cover and Natural Water Quality in the Ugii Lake Basin, Mongolia - Damdinsuren Nomindari; Sanjaa Tuya; Tamjav Bayartugs (Mongolian Geoscientist)
The Ugii Lake Basin, located in central Mongolia, has many natural parks with unique formations and is part of the International Ramsar Wetland Protection Agreement. To establish the "New Kharkhorum" city, it was necessary to plan and evaluate changes to the regional geological environment, including the Ugii Lake Basin. We aimed to assess changes in the vegetation cover, soil, and surface water of the Ugii Lake Basin. Field research, geochemical analysis of soil and surface water, and remote sensing image interpretation methods were used in this study. We interpreted Moderate Resolution Imaging Spectroradiometer satellite data from 2000 to 2022 to investigate changes in vegetation cover. On the basis of this classification, soil and natural water samples were chosen for onsite observations at four locations. As a result, the boundaries of the Ugii Lake Basin have been defined; they are 1017 km long and cover an area of 14,300 km2. Six normalized difference vegetation index categories were identified while the vegetation cover quality in the Ugii Lake Basin was assessed. The pH values of the surface water exceeded the standard by 0.05–0.21 in the area with a high anthropogenic load, whereas the other factors (Ca2+, Mg2+, Na++K+, SO42-, Fe, CI-, CO32-, HCO3-, NO2-, NO3-, and physiochemical parameters) did not exceed the Mongolian National Standard. The pH values in natural water were relatively high near the lake, indicating human activity in the Ugii Lake Basin. Consequently, this should be considered when designing integrated measures to address climate change and anthropogenic impacts in the Ugii Lake Basin.